THE ROLE OF OLIGARCHY IN LOCAL ELECTIONS FUNDING: A CASE STUDY OF CENTRAL SULAWESI - La Husen Zuada; Yulizar Pramudika Tawil; M. Kafrawi (Asia-Pacific Journal of Elections and Democracy, 2021)
How do oligarchs finance local elections, and what motivates their involvement? This study aims to examine the involvement of oligarchs in funding elections campaigns in Central Sulawesi. The research design uses case studies. This study found that oligarchs were, directly and indirectly, involved in local election activities. They become part of candidates’ campaign teams, finance political activities, play a role in issuing parties’ recommendations, mobilise mass campaigns, pay political consultants, control public opinion, distribute social assistance and design political parties coalitions. The involvement of oligarchs in local election activities is motivated by their desire to promote political parties in Central Sulawesi and the interests of running a business. This orientation of growing political parties is more dominant in influencing oligarchs to be involved in local elections, rather than the orientation of maintaining their business continuity. This finding shows that there is a shift in the orientation of entrepreneurs in providing political support. From previously conducting such support secretly, now oligarchs are bolder to appear in public as administrators of political parties, success teams and supporting political financing.